CoCu: A new short questionnaire to evaluate diet composition and culture of eating in children and adolescents. Issue 6 (December 2019) - Poulain, Tanja; Spielau, Ulrike; Vogel, Mandy; Körner, Antje; Kiess, Wieland
Summary: Background & aims: The aim of this project was to develop and validate a short questionnaire (titled CoCu – Composition and Culture of Eating) for assessing the composition of the diets of children and adolescents, and their culture of eating. We also investigated whether what and how children eat is associated with their age, gender, and social background. Methods: The "diet composition" part of the developed questionnaire contains 14 questions about the number of portions of different food products the subject child eats per week or per day. The selection of food products was based on food groups assessed in a Food Frequency Questionnaire (FFQ). The "culture of eating" part asks five questions about how children eat (e.g., number of meals, frequency of shared dinners). A total of 1604 questionnaires were completed within the framework of the LIFE Child study in Leipzig, Germany, with 741 questionnaires regarding a child aged between 10 and 19 (self reporting) and 863 regarding a child aged between 2 and 9 (parent reporting). In a subsample (n = 212 for the parent-report group and 188 for the self-report group), retest reliability was assessed by correlating answers given at two consecutive study visits (one year apart). In another subsample of the self-report group (n = 105), the validity of the questionnaire was assessed by comparing answers in CoCu with answers in the FFQ. Multiple regression analysis was used to assess whether aspects of diet composition and the culture of eating were associated with child age, gender, and social background. Results: The analyses revealed significant positive correlations between responses given at two consecutive study visits as well as significant positive correlations between the CoCu data and the FFQ. Furthermore, both the composition of the children's diets and their eating culture were found to vary significantly depending on child age, gender, and social background. Conclusions: The proposed short nutrition questionnaire represents a useful, inexpensive, and time-efficient tool for surveying the diets of children and adolescents. Highlights: The questionnaire can be used to calculate an index of the overall healthiness of a child's diet. The questionnaire displays good retest reliability and good construct validity. Children from families with a higher SES report a healthier diet. Diet healthiness decreases before adolescence but increases during adolescence. Adolescent girls report a healthier diet than adolescent boys.